1997
DOI: 10.1098/rspb.1997.0156
|View full text |Cite
|
Sign up to set email alerts
|

The origins and relatedness of multiple reproductives in colonies of the termiteNasutitermes corniger

Abstract: Colonies of the termite Nasutitermes corniger often contain multiple reproductive queens and kings. We used double-strand conformation polymorphism (DSCP) analysis of mitochondrial DNA (mtDNA) to determine the probable origins of co-occurring reproductives. Colonies di¡ered in queen and king number, in the number of nests containing reproductives, and in the genetic relationships among reproductives. Most of the 44 colonies contained a single pair of maternally unrelated reproductives. In the two single-nest c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 28 publications
2
78
0
Order By: Relevance
“…Genetic studies of other termites have shown that the degree of relatedness of the founders in monogamous colonies (simple families) varies among species and populations within the same species. Simple family colonies of Nasutitermes corniger Motschulsky (Atkinson and Adams 1997), Schedorhinotermes lamanianus Sjostedt (Husseneder et al 1999), R. )avipes, R. virginicus and R. hesperus are generally headed by a pair of unrelated colony founders, whereas the reproductive pairs of R. hageni and R. malletei colonies are often related (Copren 2007, Vargo and Carlson 2006, Vargo et al 2006b, Parman and Vargo 2008. In a French population of R. grassei, simple family colonies had closely-related reproductives (DeHeer et al 2005) whereas unrelated reproductives were found in colonies of a Portuguese population (Nobre et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies of other termites have shown that the degree of relatedness of the founders in monogamous colonies (simple families) varies among species and populations within the same species. Simple family colonies of Nasutitermes corniger Motschulsky (Atkinson and Adams 1997), Schedorhinotermes lamanianus Sjostedt (Husseneder et al 1999), R. )avipes, R. virginicus and R. hesperus are generally headed by a pair of unrelated colony founders, whereas the reproductive pairs of R. hageni and R. malletei colonies are often related (Copren 2007, Vargo and Carlson 2006, Vargo et al 2006b, Parman and Vargo 2008. In a French population of R. grassei, simple family colonies had closely-related reproductives (DeHeer et al 2005) whereas unrelated reproductives were found in colonies of a Portuguese population (Nobre et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, understanding eusociality in Isoptera may depend on empirical evidence from genetic studies and a better understanding of the diversity and evolutionary changes in termite breeding structure. To this end, there is a growing number of population genetic studies involving termites (Reilly, 1987;Atkinson and Adams, 1997;Thompson and Hebert, 1998;Husseneder et al, 1999Husseneder et al, , 2002Jenkins et al, 1999;Bulmer et al, 2001;Goodisman and Crozier, 2002;Vargo, 2003;Vargo et al, 2003Vargo et al, , 2006aDeHeer and Vargo, 2004;DeHeer et al, 2005;Dronnet et al, 2005;Hacker et al, 2005;Husseneder et al, 2005;Vargo and Carlson, 2006). The results of such studies have greatly increased our understanding of termite colony structure.…”
Section: Introductionmentioning
confidence: 96%
“…The only difference with the ants, bees and wasps is that males have similarly long lifespans to queens and that mating continues throughout life. Exceptions to this rule may occur in evolutionarily derived termite lineages where multiple breeders are sometimes found (Thorne 1983(Thorne , 1985Roisin 1987;Darlington 1988;Atkinson & Adams 1997;Thompson & Hebert 1998;Brandl et al 2001;Hacker et al 2005;Atkinson et al 2008), but no cases of effective re-mating promiscuity followed by successful colony continuation appear to have been documented with genetic markers. Issues of matechoice and sexual selection during swarming (e.g.…”
Section: Evidence For Ancestral Lifetime Monogamy In Eusocial Lineagesmentioning
confidence: 99%
“…This appears consistent with the data as multiple breeders, although reported from tens of termite species, are almost always a rare and facultative phenomenon at the population level (Thorne 1985;Roisin 1987). Given these interesting differences between the ants and the termites, it would be of paramount importance to critically evaluate the sparse records on multiple breeders in colonies of the higher termites (Thorne 1983(Thorne , 1985Roisin 1987;Darlington 1988;Atkinson & Adams 1997;Thompson & Hebert 1998;Brandl et al 2001;Hacker et al 2005;Atkinson et al 2008) to ascertain that: 1. They are derived from unrelated co-founders for each of the sexes, rather than being secondary reproductives produced by a single founding pair; 2.…”
Section: Predictions Of the Monogamy Window Hypothesismentioning
confidence: 99%